Lessons from the implementation of the Volcker Rule for banking structural reform in the European Union - Douglas J. Elliott; Christian Rauch (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
In the United States, on April 1, 2014, the set of rules commonly known as the Volcker Rule, prohibiting proprietary trading activities in banks, became effective. The implementation of this rule took more than three years, as proprietary trading is an inherently vague concept, overlapping strongly with genuinely economically useful activities such as market-making. As a result, the final Rule is a complex and lengthy combination of prohibitions and exemptions. In January 2014, the European Commission put forward its proposal on banking structural reform. The proposal includes a Volcker-like provision, prohibiting large, systemically relevant financial institutions from engaging in proprietary trading or hedge fund-related business. This paper offers lessons to be learned from the implementation process for the Volcker rule in the US for the European regulatory process.
urn:nbn:de:hebis:30:3-335131
Keywords: 330; banking separation proposals; proprietary trading ban; Dodd-Frank Act